2016
DOI: 10.1016/bs.irn.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Neuronal Tolerance of Diabetic Stress

Abstract: The etiology of diabetic peripheral neuropathy (DPN) involves an inter-related series of metabolic and vascular insults that ultimately contribute to sensory neuron degeneration. In the quest to pharmacologically manage DPN, small molecule inhibitors have targeted proteins and pathways regarded as “diabetes specific” as well as others whose activity are altered in numerous disease states. These efforts have not yielded any significant therapies, due in part to the complicating issue that the biochemical contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 152 publications
(231 reference statements)
0
2
0
Order By: Relevance
“…The potential for aHSP70 to serve as a treatment for T2DM and AD is great (Emery and Dobrowsky, 2016). That source may have advantages over recombinant human protein preparations because it can be produced in large quantities at lower cost and is categorized as a derivative of a natural food product by regulatory agencies.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for aHSP70 to serve as a treatment for T2DM and AD is great (Emery and Dobrowsky, 2016). That source may have advantages over recombinant human protein preparations because it can be produced in large quantities at lower cost and is categorized as a derivative of a natural food product by regulatory agencies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as of now, the only recommendation for preventing or slowing the progression of peripheral neuropathy is to maintain close glycemic control. It has also been suggested that pharmacological activation of protective neuronal circuits may be useful for increasing tolerance to the hyperglycemic condition and for promoting neuronal recovery [44].…”
Section: Discussionmentioning
confidence: 99%